Weak stem under shade reveals the lignin reduction behavior - Sajad Hussain; Nasir Iqbal; Ting PANG; Muhammad Naeem Khan; Wei-guo LIU; Wen-yu YANG (Journal of Integrative Agriculture, 2019)
Shades caused by neighboring tall plants in intercropping systems and weak sunlight are constraints in yield optimization. Shade influences many aspects of plant growth and development, leading to weak stems and susceptibility to lodging. The plant cell wall is composed of certain proteins that allow the walls to stretch out, a process called cell wall loosening. Shade affects anatomical, morphological, and physiological traits of plants, thus reducing the physical strength of the stem in crops by changing the loosening of cell walls. Flexibility of cells facilitates further modifications such as wall loosening. In addition, shade stress causes increased internode length, and reduced xylem synthesis and photosynthesis. In shaded plants, lignin deposition in vascular bundles and sclerenchyma cells of stems is decreased. Lignin is a light sensitive phenolic compound and shading decreases the transcript abundance of several phenolic compound (flavone and lignin) related genes. Shading significantly influences the metabolic activities of phenylalanine ammonia-lyase (PAL), peroxidase (POD), 4-coumarate: CoA ligase (4CL), and cinnamyl alcohol dehydrogenase (CAD) involved in lignin biosynthesis. Furthermore, suppression of lignin biosynthesis activities by abiotic stresses causes abnormal phenotypes such as collapsed xylem, bent stems, and growth retardation. In this review, the underlying mechanisms illustrate that under shading conditions reduced lignin content results in slender, weak, and unstable stems. The objective of this review is to elaborate lignin biosynthesis and its variability under stressful environmental conditions, especially in shade stress environments. The effects of shade on stem lignin metabolism are discussed on the morphogenetic, physiological, and proteomic levels.